Experimental study on orthogonal joints in cross-laminated timber with self-tapping screws installed with mixed angles. (1st February 2021) - Brown, Justin R.; Li, Minghao; Tannert, Thomas; Moroder, Daniel
Highlights: Fifty-nine cross-laminated timber orthogonal joints with screws were tested. Joints with mixed angle screws achieved high ductility and energy dissipation. Overstrength and ductility of screwed joints were determined. Available strength models for screwed joints were adequate to predict capacity. Abstract: Cross-laminated timber (CLT) is increasingly being used in lateral load resisting systems of multi-storey buildings. Conventional in-plane CLT shear walls can be transformed into CLT core-wall structures with enhanced lateral strength and stiffness when the individual walls are connected orthogonally. In this paper, experimental studies are presented on orthogonal CLT joints with self-tapping screws (STS) installed with mixed angles, i.e. different installation angles between the STS axis and the plane of the CLT surface. A total of 59 orthogonal joint specimens were tested in 9 different configurations to derive the relevant joint performance parameters from monotonic and cyclic tests. The joint specimens used five-layer and seven-layer CLT panels connected by ∅8 mm or ∅12 mm STS. Different ratios of STS installed inclined and STS installed at 90° to the CLT surface were investigated to determine an optimum ratio of STS for enhanced joint performance. It was found that a ratio of one 90° STS for every two inclined STS ensured significant increase in ductility and displacement capacity of approximately three times when compared to specimens with only inclined STS. A minimum moderate ductility was achieved in all test series where the primary failure mode was STS withdrawal. It was found that 90° STS contributed to both strength and stiffness in joints that also contained inclined STS. The average experimental overstrength was 1.7 for most joint configurations. Existing analytical models were adequate in estimating strength but inadequate to estimate stiffness.